2003
DOI: 10.1046/j.1365-2559.2003.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

p57kip2 is useful in the classification and differential diagnosis of complete and partial hydatidiform moles

Abstract: In summary, p57kip2 immunostaining results correlated well with morphological features of molar pregnancies and were helpful in determining histologically equivocal cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 15 publications
7
37
1
Order By: Relevance
“…This cyclin-dependent kinase inhibitor, which is paternally imprinted, was recently shown to be a useful tool for the diagnosis of CHM because its expression is primarily absent in villous cytotrophoblasts. 40 According to these criteria, p57KIP2 was found to be expressed in 0 to 1.5% of villous cytotrophoblasts of 11 placentas, confirming CHM, whereas two placentas were excluded from further investigations because p57KIP2 expression was observed in more than 7% of villous cytotrophoblasts. Representative examples of villi from CHM placentas lacking p57KIP2 expression are shown ( Figure 7A).…”
Section: Elevated Expression Of Nuclear ␤-Catenin In Extravillous Tromentioning
confidence: 97%
See 1 more Smart Citation
“…This cyclin-dependent kinase inhibitor, which is paternally imprinted, was recently shown to be a useful tool for the diagnosis of CHM because its expression is primarily absent in villous cytotrophoblasts. 40 According to these criteria, p57KIP2 was found to be expressed in 0 to 1.5% of villous cytotrophoblasts of 11 placentas, confirming CHM, whereas two placentas were excluded from further investigations because p57KIP2 expression was observed in more than 7% of villous cytotrophoblasts. Representative examples of villi from CHM placentas lacking p57KIP2 expression are shown ( Figure 7A).…”
Section: Elevated Expression Of Nuclear ␤-Catenin In Extravillous Tromentioning
confidence: 97%
“…All cases were further investigated by immunohistochemical p57KIP2 staining as previously mentioned. 40,41 Cultivation of Cell Lines JEG-3 choriocarcinoma cells and trophoblastic SGHPL-5 were cultivated in Dulbecco's modified Eagle's medium (DMEM) and in a 1:1 mixture of DMEM and Ham's F-12, respectively, supplemented with 10% fetal calf serum, 2 mmol/L glutamine, and 0.05 mg/ml gentamicin (all purchased from Invitrogen, Carlsbad, CA) as previously mentioned.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…PCR amplification of nine short tandem repeat loci from eight different chromosomes (chromosomes 2,3,4,5,7,11,12,13) and the amelogenin locus (for XY determination) was performed, with thermal cycling conditions and capillary electrophoresis carried out according to the manufacturer's instructions (AmpFlSTR Profiler kit; Applied Biosystems; Foster City, CA). In certain selected situations (see results), an expanded analysis with PCR amplification of 15 short tandem repeat loci from 13 different chromosomes (chromosomes 2, 3,4,5,7,8,11,12,13,16,18,19,21) and the amelogenin locus (for XY determination) was performed (AmpFlSTR Identifiler kit; Applied Biosystems). The PCR conditions were 95 1C for 11 min followed by 28 cycles of 94 1C for 1 min, 59 1C for 1 min, and 72 1C for 1 min, followed by a final extension at 60 1C for 45 min.…”
Section: Diagnosis Of Hydatidiform Molesmentioning
confidence: 99%
“…However, previous studies have demonstrated that diagnosis of hydatidiform moles based on morphology alone, even by experienced pathologists with specialized training, is subject to interobserver variability and therefore suboptimal diagnostic reproducibility. [9][10][11][12][13][14][15] A number of studies have demonstrated the value of ancillary techniques, including immunohistochemical analysis of cyclin-dependent kinase inhibitor 1C (CDKN1C/p57/Kip2, the protein product of the CDKN1C imprinted gene located at chromosome 11p15.5; referred to henceforth as p57) expression [16][17][18][19][20][21][22][23][24][25][26][27] and molecular genotyping via PCR amplification of short tandem repeat loci, 23,25,[28][29][30][31] for improving the diagnosis of hydatidiform moles. Genotyping is particularly valuable because it allows for specific distinction of complete hydatidiform moles, partial hydatidiform moles, and nonmolar specimens from one another due to their unique genetics.…”
mentioning
confidence: 99%
“…KIP2 has been shown to be a highly sensitive marker for the differential diagnosis of complete from partial hydatidiform mole (191)(192)(193)(194)(195)(196)(197).…”
Section: Kip2mentioning
confidence: 99%